2008
DOI: 10.2737/rmrs-rn-35
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil seed bank characteristics in ponderosa pine forests using vegetation and forest-floor data

Abstract: Abstract-Soil seed banks are important for vegetation management because they contain propagules of species that may be considered desirable or undesirable for site colonization after management and disturbance events. Knowledge of seed bank size and composition before planning management activities facilitates proactive management by providing early alerts of exotic species presence and of abilities of seed banks to promote colonization by desirable species. We developed models in ponderosa pine (Pinus ponder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Using a systematic gradient design might be useful to explore potential finer-scale variation in seed banks in our study area. Lack of relationship between seed banks and site-level tree canopy cover contrasts sharply with a previous study 250 km to the south-east of ours, on a P. ponderosa forest landscape, where seed density was threefold greater below open compared to dense canopies (Abella and Springer, 2008). Some previous studies in western USA coniferous forests found that, contrasting with our results, seed banks differed among ecosystem and forest types within landscapes (Kramer and Johnson, 1987;Abella et al, 2007).…”
Section: Environment and Vegetationcontrasting
confidence: 99%
“…Using a systematic gradient design might be useful to explore potential finer-scale variation in seed banks in our study area. Lack of relationship between seed banks and site-level tree canopy cover contrasts sharply with a previous study 250 km to the south-east of ours, on a P. ponderosa forest landscape, where seed density was threefold greater below open compared to dense canopies (Abella and Springer, 2008). Some previous studies in western USA coniferous forests found that, contrasting with our results, seed banks differed among ecosystem and forest types within landscapes (Kramer and Johnson, 1987;Abella et al, 2007).…”
Section: Environment and Vegetationcontrasting
confidence: 99%
“…Our results highlighted that effective passive restoration soon after bush clearing depends upon seed production, particularly of early successional species rather than persistent seed bank. Under these circumstances, post-clearing management of aboveground vegetation including protection of already existing vegetation is key to increase seed production and species richness (Abella and Springer 2008). In general, similarity between SSB and AGV at Kgomokgomo was low although it increased with time in cleared microsites (Fig.…”
Section: Similarity Between Ssb and Agv In The Cleared And Uncleared Micrositesmentioning
confidence: 96%